Optimization of regasified liquefied natural gas based reforming process for syngas production in an ammonia plant. Issue 13 (2nd July 2020) - Sunny, Anju; Gazliya, N.; Aparna, K.
ABSTRACT: The present work optimize the reforming process for syngas production in regasified liquefied natural gas (R-LNG) based ammonia plant using central composite design in response surface methodology and then to perform a comparison study with the optimization results obtained from the Aspen HYSYS simulation and experimental plant data. The optimization study has been conducted based on the effect of six independent parameters including feed input temperature, feed input pressure, wall temperature of the reformer tube, steam to carbon ratio, hydrogen to carbon ratio and R-LNG feed flow rate on two responses, hydrogen production and amount of unreacted methane in the output stream. Finally, the optimum values of the process variables have been recorded, which results in maximum hydrogen concentration and minimum methane content in the output stream. The average error was about 6.7% for RSM model, and it was approximately 3.8% for HYSYS model, which implies that the discussed models have an acceptable validity. Abbreviations : ANOVA: Analysis of Variance; CCD: Central Composite Design; CHR: Carbon to Hydrogen Ratio; FACT: Fertilisers And Chemicals Travancore Limited; GHR: Gas Heated Reformers; HYSYS: Hyprotech System Metric Ton Per Day; OFAT: One-Factor-at-A-Time; PBD: Plackett–Burman Design; PFD: Process Flow Diagram; PR: Peng-Robinson; R-LNG Regasified Liquefied Natural Gas; RSM: Response Surface Methodology